Pharmacoresistance in psychiatry - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2009)
Pharmacoresistance (resistance to treatment) is one of the major problems in psychiatry although several new drugs come into clinical practice every day. There is a role of genetic factors, change in cellular response and change in nature of the disorder in patients who are individually treatment resistant. It is important to understand reasons of pharmacoresistance not only for effectiveness but also for polypharmacy required situations and for pharmacoeconomy. The more we learn about pharmacoresistance it will be possible to consider all factors from drugs, patients and disease therefore, rational drug use and/or rational polipharmacy will be provided.
Keywords: CYP 450 enzymes; monoamine transporters; G proteins; P-glycoprotein; Multidrug resistance protein; drug interactions; neuroplasticity; neurotrophins; cytokines; BIPOLAR DISORDER; SCHIZOPHRENIA; POLYMORPHISMS; ASSOCIATION; GENES; PLASTICITY; FEMALES; BRAIN; DRUGS